2007
DOI: 10.1002/asia.200700032
|View full text |Cite
|
Sign up to set email alerts
|

The First Cyclopentadienylalkylphosphane Nickel Chelates: Synthesis, Structures, and Reactions

Abstract: The first cyclopentadienylalkylphosphane nickel chelate complexes are reported. The anionic ligand obtained by reaction of spiro[2.4]hepta-4,6-diene with lithium di-tert-butylphosphide was treated with NiCl2 to yield [eta(5):kappa(1)-(di-tert-butylphosphanylethyl)cyclopentadienyl]chloronickel(II). From this complex, some acetonitrile-stabilized cationic complexes were obtained by reaction with the respective silver salts in acetonitrile. Methyl- and alkynylnickel chelates were prepared by reaction of the chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 73 publications
2
35
0
Order By: Relevance
“…This is based on a comparison with the data of related di- tert-butyl-substituted complexes 3 and 6, which show respective resonances around 90 ppm, [11,13] assuming a shielding effect of the silyl substituent as compared to a tert-butyl group. In the 31 P{H} NMR spectra, singlets at δ = 24.0, 24.9, and 25.4 ppm, respectively, were observed, indicating a coordinated silylphosphane tether with nickel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is based on a comparison with the data of related di- tert-butyl-substituted complexes 3 and 6, which show respective resonances around 90 ppm, [11,13] assuming a shielding effect of the silyl substituent as compared to a tert-butyl group. In the 31 P{H} NMR spectra, singlets at δ = 24.0, 24.9, and 25.4 ppm, respectively, were observed, indicating a coordinated silylphosphane tether with nickel.…”
Section: Resultsmentioning
confidence: 99%
“…Deprotonation, reaction with spiro[2.4]hepta-4,6diene, followed by treatment with nickel dihalide complexes www.eurjic.org FULL PAPER 1989; [9] 2 bears an internal amine ligand and was prepared by Hadjiliadis et al in 1998; [10] 3 represents a cyclopentadienylalkylphosphane nickel chelate and was prepared in our group in 2007; [11] 4 is a cationic chelate with sulfur coordination, which was prepared by Rauchfuss et al in 1985, [12] and alkene complex 5 was prepared by Okuda et al. Only a few representatives of such complexes with early-transition-metals are known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 With the new tert-butylphenyl substituted ligand in hand, we prepared the respective nickel chelate rac-20 in 70% yield. rac-20 was characterized spectroscopically, all data are in accord with related complexes.…”
mentioning
confidence: 99%
“…rac-20 was characterized spectroscopically, all data are in accord with related complexes. 15,16 Jolly et al reported the synthesis of cyclopentadienylchromium dichloride chelates with a phosphane tether and their application as catalysts in alkene oligo-and polymerization reactions. 76 The complexes reported bear identical substituents at phosphorus, crystal structure analyses of the diphenyl and the dicyclohexyl complexes were included.…”
mentioning
confidence: 99%